2016
DOI: 10.1093/deafed/enw072
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Facial Emotion Recognition in Deaf Children

Abstract: This exploratory research is aimed at studying facial emotion recognition abilities in deaf children and how they relate to linguistic skills and the characteristics of deafness. A total of 166 participants (75 deaf) aged 3-8 years were administered the following tasks: facial emotion recognition, naming vocabulary and cognitive ability. The children's teachers or speech therapists also responded to two questionnaires, one on children's linguistic-communicative skills and the other providing personal informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 44 publications
4
19
1
3
Order By: Relevance
“…In contrast to some previous studies, no relationship was found between language ability and emotion recognition (e.g. Dyck et al, 2004;Sidera et al, 2016). This may indicate that the visual and contextual cues are sufficient for deaf children to recognise emotions when using ecologically valid stimuli in the domain of emotion recognition.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…In contrast to some previous studies, no relationship was found between language ability and emotion recognition (e.g. Dyck et al, 2004;Sidera et al, 2016). This may indicate that the visual and contextual cues are sufficient for deaf children to recognise emotions when using ecologically valid stimuli in the domain of emotion recognition.…”
Section: Discussioncontrasting
confidence: 91%
“…The current finding that deaf children perform similarly to their hearing peers in middle childhood is consistent with the studies of Hosie et al (1998), Hopyan-Misakyan et al (2009 and Most and Aviner (2009), but contrasts with the findings of Dyck et al (2004), Ludlow et al (2010) and Sidera et al (2016). In addition to the extra social information that our stimuli provided by using real human and dynamic faces, it is noteworthy that the children in our study were within the normal range in their non-verbal intellectual ability.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…So much so that it has been found that language explains the variance in emotional comprehension better than age or family environment [25]. In particular, Ruffman et al [35] demonstrated that performance in syntax correlates positively with facial emotion recognition; and Sidera et al [36] found that facial emotion recognition correlated with receptive vocabulary and linguistic and communicative abilities. On the other side, Pons et al [31] found a high correlation between grammar abilities and emotion comprehension in children aged from 4 to 11 years, and Vilches [37] identified a positive influence between reading competence and EI, arguing that through reading students have access to roles played by different characters in various scenarios that enable them to respond emotionally to their own thoughts and feelings.…”
Section: Emotional Intelligence and Languagementioning
confidence: 99%